POSSIBILITIES OF INTEGRATING SUSTAINABLE DEVELOPMENT AS SUBJECT IN ROMANIAN HIGHER EDUCATION’S CURRICULA (PANGEEA, 2025)
Seriousness of the problems focused on the protection and quality of the environment at the national and international levels imposes the need for urgent changes in educational systems of many countries. Modern educational theory, practice and recommendations of international organizations call for introducing basic aspects regarding sustainable development and environment protection. In order to understand the need and the importance of environmental factors and laws in the professional domain, the connection between environmental and professional aspects of students’ future professional activities is necessary to understand environmental protection as a necessary content and principle of educational work at the university. In the paper, the educational needs of different groups of the academic population are synthesized; in fact, the program’s educational orientation for environmental protection in higher education is shown.
Keywords: environment; sustainable development; higher education; educational needs